Effects of a short-term molt using cassava meal, broken rice, or corn meal on plasma thyroxin concentrations, organ weights and intestinal histopathology in older (95 wk) laying hens - Gongruttananun, Nirat; Guntapa, Panaput; Saengkudrua, Kanokporn; Boonkaewwan, Chaiwat (Agriculture and Natural Resources, 2017)
The effects of a nonfasting induced molt were determined on the thyroxin concentration, organ weight and intestinal histopathology in 95-wk-old hens. Hens (60 birds each treatment) were randomly assigned to four treatments for 14 d: 1) molted by feeding broken rice (BRO), 2) fed corn (COR), 3) fed cassava (CAS), or 4) a non-molt control (NON). During the molt period, the BRO, COR and CAS groups were exposed to an 8 h light: 16 h dark photoperiod, whereas the control hens were fed a layer ration and provided with 16 h of light per day. The body weight loss in the CAS hens was 21.90% which was significantly higher than those of the BRO (6.01%) or COR hens (9.30%). The CAS hens completely stopped laying on d 7, whereas the BRO and COR birds exhibited reductions but continued laying. The egg weight of the COR treatment was significantly lower than those of the BRO and CAS treatments. At the end of the molt period, the hematocrit values of the BRO and CAS hens were significantly higher than those of the COR hens. The plasma thyroxin concentrations of the CAS treatment were significantly higher than those of the COR treatment, whereas the BRO hens had a value intermediate between the two groups. The CAS and COR hens had reduced liver weights compared with the BRO hens. However, the thyroid weights of the CAS and COR hens were significantly greater than those of the BRO hens. No inflammatory evidence was observed in any treatment from the examination of intestinal histopathology.